PENGUATAN KERJASAMA POLA KEMITRAAN ANTARA PEMERINTAH DAERAH, SWASTA DAN MASYARAKAT DALAM PENGEMBANGAN SEKTOR PARIWISATA DI KABUPATEN MANOKWARI PROVINSI PAPUA BARAT - , Edison Bebari, S.Sos ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Synergy between local government, private institution and society in realizing good governance is a agenda toward bureaucracy and public administration reformation. Government will face smarter people that more demand better service. In heterogeneous society, role of government will be increasingly less and no dominate and monopolize but empowering people participation in driving macro and micro economic sector. Role of local government as regulator, stabilizer and facilitator is required as local leader to bridge and balance business actors desire and public interest in order not to distortion and stagnation. Management of tourism industry as a chain link of economy is not separated from social cultural condition in local area. This research was intended to describe and analyze partnership pattern between local government, private institution and society in Manokwari in developing tourism industry and to understand role of each actor as well as to identify factors influencing partnership pattern. This research used descriptive qualitative method and data collected through in-depth interview, observation and documentation. Data source is local government represented by the Regend and official of institution related to tourism, tourism business actor and society care tourism using purposive sampling determined for certain persons. Result of analysis and discussion indicated that there are some patterns of partnership between local goverment, and private institution consisting of nucleus- plasma, sub contract pattern, general trading pattern, franchise pattern and agency pattern in developing tourism industry. The partnership have not run effectively in which local original revenue only come from hotel and restaurant tax, while contribution from tourism object was not optimal. Weak coordination between cultural and tourism office and other institution in cross sectoral cooperation was not harmonic in which startegy implementation have not appropriate. Human resource for tourism promotion is weak. In addition, product readiness and market oppotunity has not been organized well. Partnership cooperation in developing tourism industry was still done by contract system. The trickle down effect of the cooperation has not directed to give positive impact for people economic growth. It is recommended that local government of Manokwari regency should make policy on local tourism development plan and tourism object development plan as detail of sustainable tourism development. Then, it should increase tourism ad leading sector by making regulation on local tourism, partnership cooperation and pro-tourism budgeting policy, so people will benefit from the trickle down effect. For success implementation of a policy or program, government should do survey first to gather data and information and to accommodate people need to encourage people participation.